Finasteride therapy in a dog with benign prostatic hyperplasia - Hyejin Kim (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Benign prostatic hyperplasia (BPH) is frequently observed in intact middle-aged or older male dogs with symptoms ranging from asymptomatic to various symptoms such as urination, dyschezia, dysuria, tenesmus, and intermittent serosanguinous or clear serous exudate. A 4-year-old, intact male Welsh corgi with symptoms of intermittent hematuria and serosanguinous exudate at the urethral opening was diagnosed with BPH and intraprostatic hematocyst through ultrasonographic examination and cytology test. The dog was internationally adopted for reproductive purposes and needed to undergo BPH treatment while maintaining fertility. Thus, 2.5 mg finasteride was administered orally once a day for treatment option and therapeutic effects were observed, including loss of clinical symptoms and reduced prostate and intraparenchymal cyst size.